Pickle water ameliorates castor oil-induced diarrhea in mice by regulating the homeostasis of the gut microbiota and intestinal mucosal barrier - Zhou, Tian; Long, Dongmei; Zhou, Maoting; Hu, Xianghong; Wang, Yu; Wang, Xing (Frontiers in Nutrition, 2024)
Diarrhea is a common clinical condition that can potentially be fatal. Current treatment options often have side effects, such as constipation and vomiting, and effective therapies for diarrhea are lacking. Pickled vegetables are a famous traditional food in China. Clinical studies suggest that pickle water (PW) can alleviate diarrhea in children; however, its pharmacological effects and mechanisms on intestinal health remain unclear. Here, this study aimed to explore the protective effects of PW on castor oil-induced diarrhea in ICR mice and investigate its potential mechanisms. Castor oil-induced diarrheal models were used to evaluate the antidiarrheal effects of PW. During the experiment, the indexes to evaluate the degree of diarrhea were determined. After euthanizing the mice, oxidative stress indices in the ileum were assessed using biochemical methods, and the expression of tight junctionrelated proteins in the ileum was analyzed by Western blot. The 16S rRNA high-throughput sequencing technology was applied to evaluate the diversity and composition of intestinal flora. The results showed that PW supplementation reduced body weight without significantly affecting organ index and liver function in castor oil-induced diarrhea mice. Meanwhile, PW effectively reduced the dilution rate, diarrhea index, average loose stool grade, propelling distance of carbon powder and intestinal propulsive rate, along with improved the pathological abnormality of ileum. Furthermore, PW enhanced the activities of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), catalase (CAT), and reduced the malonaldehyde (MDA) levels. PW increased the protein zonula occludens-1 (ZO-1) and occludin expression in the ileum. Additionally, the analysis of 16S rDNA revealed that PW increased the α diversity and β diversity, ameliorated intestinal flora composition and restored that to normal level. Collectively, dietary PW administration ameliorates Castor oil-induced diarrhea by restoring the tight junctions between intestinal mucosal cells, suppressing oxidative stress and regulating the composition of intestinal flora. These findings suggest that PW may be a promising strategy for managing diarrhea.